Ain't no trust: how bosses, boyfriends, and bureaucrats fail low-income mothers and why it matters - Levine, Judith A (University of California Press, 2013)
Ain’t No Trust explores issues of trust and distrust among low-income women in the U.S.—at work, around childcare, in their relationships, and with caseworkers—and presents richly detailed evidence from in-depth interviews about our welfare system and why it’s failing the very people it is designed to help. By comparing low-income mothers’ experiences before and after welfare reform, Judith A. Levine probes women’s struggles to gain or keep jobs while they simultaneously care for their children, often as single mothers. By offering a new way to understand how structural factors impact the daily experiences of poor women, Ain’t No Trust highlights the pervasiveness of distrust in their lives, uncovering its hidden sources and documenting its most corrosive and paralyzing effects. Levine’s critique and conclusions hold powerful implications for scholars and policymakers alike.